2022
DOI: 10.3390/plants11111504
|View full text |Cite
|
Sign up to set email alerts
|

Role of Litsea cubeba Essential Oil in Agricultural Products Safety: Antioxidant and Antimicrobial Applications

Abstract: The essential oil from Litsea cubeba (LCEO) has good antioxidant, antimicrobial, anti-insect properties, which gives it the potential for use as a natural additive to food resources and food products in order to prevent spoilage and extend shelf life. In this study the biological activity related to food preservation was observed. The main volatile organic compounds were geranial (39.4%), neral (29.5%), and limonene (14.3%). Antioxidant activity was 30.9%, which was equal to 167.94 µg of Trolox per mL of sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Fruit. was composed of 39.39% geranial, 29.49% neral, 14.29% α-limonene, 2.29% β-pinene, 1.89% sabinene, 1.89% 1,8-cineole, 1.69% α-pinene, 1.59% α-terpinolene and 1.32% 6-methyl-5-hepten-2-one, as major compounds adding up to 96% of the total profile [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fruit. was composed of 39.39% geranial, 29.49% neral, 14.29% α-limonene, 2.29% β-pinene, 1.89% sabinene, 1.89% 1,8-cineole, 1.69% α-pinene, 1.59% α-terpinolene and 1.32% 6-methyl-5-hepten-2-one, as major compounds adding up to 96% of the total profile [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…They reported that LCEO was highly effective against Gram-negative bacteria and proposed a mechanism of action based on damages to the cell membrane and wall. Moreover, good inhibitory effectiveness against Gram-positive bacteria has been reported from a LCEO with similar composition [ 18 , 21 , 26 ], some studies even point to a slight higher sensitivity of Gram-positive bacteria to citral [ 27 ]. Conversely, other authors, testing a LC fruit EO containing 85% citral reported that Gram-positive bacteria were far less sensitive to LCEO than Gram-negative, although in both cases it was strongly dependent on the strain [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike other woody oil plants, L. cubeba is an economically important aromatic plant on account of its essential oil, with a lemon-like scent and pungent taste, which can be commercially extracted from the fruit, flowers, leaves, bark, and even roots by conventional hydrodistillation or steam distillation methods [ 2 ]. Although L. cubeba has been widely used in traditional medicine for a thousand years [ 3 ], its essential oil rather than kernel oil is still the main industrial export product with extensive use in the fields of food [ 4 , 5 ], medicine [ 6 , 7 , 8 ], cosmetics [ 9 ], and botanical insecticides [ 10 ]. China is the largest producer of L. cubeba essential oils in the world, with a total planting area of around 1440 thousand hectares, leading to about 140.1 thousand tons of essential oils, which is equivalent to nearly USD 0.14 billion.…”
Section: Introductionmentioning
confidence: 99%